Trace mineral levels during gestation - effects on hemoglobin, performance and health of neonatal pigs - Schoneweis, D.A.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty-one litters were used to compare effects of two levels of trace minerals fed dams during gestation on hemoglobin, performance, and health of neonatal pigs. There were no significant differences in number of pigs born alive, birth weight, two-week or four-week weights of the pigs due to trace minerals fed the dams during gestation. Neither were there differences between groups of pigs in hemoglobin, packed cell volume, or erythrocytes at birth or at two-weeks age. There were no apparent differences in the incidence of diarrhea or other neonatal diseases between the two group. Our results suggest no benefits from feeding high levels of trace minerals to sows during gestation.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Trace mineral; Gestation; Hemoglobin; Performance; Neonatal pigs